The social and pedagogical bases of the realization of the state youth policy in Ukraine - Valentine Balakhtar (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article deals with the terms "youth policy" and the "state youth policy". Have been analyzed the impact of state youth policy on the social formation and youth socialization, which significantly express the tendencies of democratization and humanization of social relations, the state desire to coordinate with the interests of various strata and groups of population, public institutions and local communities. The main directions of the state youth policy due to the social formation and development of the growing youth; micro- and macro factors have been examined. The role of the social worker as the subject of realization of the state youth policy has been discovered.